Oxahelicene NHC ligands in the asymmetric synthesis of nonracemic helicenes. Issue 31 (5th April 2017) - Sánchez, Isabel Gay; Šámal, Michal; Nejedlý, Jindřich; Karras, Manfred; Klívar, Jiří; Rybáček, Jiří; Buděšínský, Miloš; Bednárová, Lucie; Seidlerová, Beata; Stará, Irena G.; Starý, Ivo
Abstract : Oxahelicene NHC ligands were used in Ni-catalysed enantioselective cycloisomerisation of alkynes to obtain helicenes in up to 86% ee. Abstract : A straightforward approach to enantiopure 2 H -pyran-modified amino[5]helicenes and amino[6]helicenes was developed. They were converted to 1, 3-disubstituted imidazolium salts and used as NHC ligand precursors in the Ni 0 -catalysed enantioselective [2+2+2] cycloisomerisation of aromatic triynes to obtain the model helicene derivatives in up to 86% ee.